Determining the Best Laboratory Head Performance: A Data-Driven Approach to Enhanced Decision Making Using the SAW Method - Evada Rustina; Nur Wening; Rianto Rianto (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
In today's fast-paced world, vocational schools play a pivotal role in shaping the future of the workforce. These schools focus on providing practical training to students, enabling them to acquire skills that are in demand in various industries. As a result, laboratory management is very important and requires attention. This study aims to determine the laboratory head's best performance. The study employs a quantitative approach, utilizing the SAW method and the Decision Support System, in addition to a descriptive analysis that compares the results of the principal's assessment with those of peers. Assessment is done using formulas that are Likert-scaled. The research was conducted at Putra Samodera Shipping Vocational School, Yogyakarta, Indonesia, where there are four laboratories, namely: a nautical laboratory, a commercial ship engineering laboratory, a language laboratory, and a computer laboratory. According to the results, the head of the commercial ship engineering laboratory performed the best. There is no difference between the assessments of the principal and peers, but the best performance according to the criteria is not the same. Other vocational schools can incorporate the implications of this study into their decision support systems and enhance them with various techniques to advance the discussion in future studies.